Valproic acid in the complex therapy of malignant tumors - Hrebackova, J; Hrabeta, J; Eckschlager, T (Current drug targets, 2010)
Valproic acid (VPA) has been used for epilepsy treatment since the 1970s. Recently, it was demonstrated that it inhibits histone deacetylases (HDAC), modulates cell cycle, induces tumor cell death and inhibits angiogenesis in various tumor models. The exact anticancer mechanisms of VPA remains unclear, but HDAC inhibition, extracellular-regulated kinase activation, protein kinase C inhibition, Wnt-signaling activation, proteasomal degradation of HDAC, possible downregulation of telomerase activity and DNA demethylation participate in its anticancer effect. Hyperacetylation of histones, as a result of HDAC inhibition, seems to be the most important mechanism of VPA's antitumor action. Preclinical data suggest that the anticancer effect of chemotherapy is augmented when VPA is used in combination with cytostatics. Besides the effects of pretreatment with HDAC inhibitors, which increases the efficiency of 5-aza-2'-deoxycytidine, VP-16, ellipticine, doxorubicin and cisplatin, pre-exposure to VPA increases the cytotoxicity of topoisomerase II inhibitors. There are two suggested cell death mechanisms caused by potentiation of anticancer drugs by HDAC inhibitors that are neither exclusive nor synergistic. The first involves apoptosis and can be both p53 dependent or independent; the second involves mechanisms other than apoptosis. In resistant chronic myeloid leukemia (CML), VPA restores sensitivity to imatinib. We have demonstrated the synergistic effects of VPA and cisplatin in neuroblastoma cells. VPA can be taken orally, crosses the blood brain barrier and can be used for extended periods. Clinical trials in patients with malignancies are being conducted. The use of VPA prior to or together with anticancer drugs may thus prove a beneficial treatment.
Keywords: histony; kombinovaná terapie; klinické zkoušky jako téma; Combined Modality Therapy; Neoplasms; chronická myeloidní leukemie; kombinovaná farmakoterapie; histondeacetylasy; chemorezistence; inhibitory topoisomerasy II; Histone Deacetylase Inhibitors; Histone Deacetylases; Azacitidine; nádorový supresorový protein p53; Drug Repositioning; Drug Synergism; Drug Therapy, Combination; přehodnocení terapeutických indikací léčivého přípravku; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; epilepsie; synergismus léků; Angiogenesis Inhibitors; lidé; inhibitory histondeacetylas; Humans; inhibitory angiogeneze; Acetylation; Tumor Suppressor Protein p53; Cell Cycle; apoptóza; acetylace; Histones; nádory; kyselina valproová; Drug Resistance, Neoplasm; buněčný cyklus; Valproic Acid; Epilepsy; Decitabine; Topoisomerase II Inhibitors; Apoptosis; azacytidin; decitabin; Clinical Trials as Topic